An update on the genus Longidorus, Paralongidorus and Xiphinema (Family Longidoridae) in Portugal - Gutiérrez-Gutiérrez, Carlos; Bravo, Maria Antonia; Santos, Margarida Teixeira; Vieira, Paulo; Mota, Manuel (Zootaxa, 2016)
The tribe Longidorini within the subfamily Longidorinae (Longidorus spp. and Paralongidorus spp.) and the subfamily Xiphineminae (Xiphinema spp.) are two large nematode groups with about 260 and 230 known species, respectively. They are globally two important groups of ectoparasitic nematodes considered to be major pests because of their activity as vectors of important plant nepovirus, with some species included in the list of quarantine pathogenic organisms in many European countries. Knowledge of the biodiversity and occurrence of this nematode group is a prerequisite for the establishment of sound management strategies and control measures. According to data collected from the databases (such as EPPO, FSTA, and Web of Science) and published in specialised literature, a total of 15 Longidorus, 1 Paralongidorus and 40 Xiphinema species have been recorded as present in Portugal. However, the taxonomic status of some species is controversial, and thus needs to be clarified. A comprehensive review for unravelling the biodiversity and occurrence of nematode species of the genus Longidorus, Paralongidorus and Xiphinema in Portugal is herein provided. This review includes an updated checklist of species with information on the localities, host plants and geographical distribution. Additionally, maps on the species distributions of Longidorinae and Xiphineminae nematodes present in Continental Portugal and the Portuguese Macaronesian islands are provided, as well as unpublished data on authors and comments on the current taxonomic status. Finally, new insights and directions for future research on Longidoridae in Portugal are presented.